2008
DOI: 10.1016/j.surfcoat.2008.08.027
|View full text |Cite
|
Sign up to set email alerts
|

Electronic origin of the isostructural decomposition in cubic M1−xAlxN (M=Ti, Cr, Sc, Hf): A first-principles study

Abstract: We have used first-principles calculations to investigate the mixing enthalpies, lattice parameters and electronic density of states of the ternary nitride systems Ti1−xAlxN, Cr1−xAlxN, Sc1−xAlxN and Hf1−xAlxN in the cubic B1 structure where the transition metals and aluminium form a solid solution on the metal sublattice. We discuss the electronic origins of the possible isostructural decomposition in these materials relevant for hard coatings applications. We find that in the systems Ti1−xAlxN and Hf1−xAlxN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
60
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 32 publications
13
60
0
Order By: Relevance
“…16͒ can be seen. Such a small overestimation of the experimental values is common for calculations using the GGA functional and a similar shape of the calculated curve was also observed in lattice parameter calculations for different related systems, such as Ti 1−x Al x N, Cr 1−x Al x N, and Hf 1−x Al x N. 24 The experimental curve ͑with red dots͒ in Fig. 6 is a combination of the compositions achieved from RBS and the lattice parameters calculated from XRD data.…”
Section: Scn͑111͒ Andsupporting
confidence: 74%
See 2 more Smart Citations
“…16͒ can be seen. Such a small overestimation of the experimental values is common for calculations using the GGA functional and a similar shape of the calculated curve was also observed in lattice parameter calculations for different related systems, such as Ti 1−x Al x N, Cr 1−x Al x N, and Hf 1−x Al x N. 24 The experimental curve ͑with red dots͒ in Fig. 6 is a combination of the compositions achieved from RBS and the lattice parameters calculated from XRD data.…”
Section: Scn͑111͒ Andsupporting
confidence: 74%
“…19 Calculations estimate the indirect band gap to be 0.9-1.6 eV ͑Refs. 20-23͒ and the lattice parameter to be 4.521 Å, 24 while experimentally the lattice parameter is measured to be 4.50 Å. 25 Its thermodynamically stable crystal structure is rocksalt, even though it is also predicted to form a metastable hexagonal phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14][15] This is believed to be responsible in part for the improved wear resistance of TiAlN coatings which has been extensively studied both experimentally [12,13,15] and theoretically. [12,[15][16][17][18] During growth, limited short-range clustering is likely to occur [19] and must be taken into account in order to obtain a complete atomistic understanding of these materials.…”
Section: Introductionmentioning
confidence: 99%
“…One such well studied example is (TiAl)N which is known to go from a solid solution phase of c-(TiAl)N to a phase separated state with a mixture of c-TiN and c-AlN upon heating, a process that drastically improves resultant material properties. [1][2][3][4][5][6][7] However, additional heating, around 900 • C, will deteriorate the material properties when the AlN changes its structure from cubic to wurtzite. 8 In our previous works [9][10][11] we demonstrated that the addition of Cr into the solution leads to a formation of intermediate metastable phases of (TiCr)N and (CrAl)N where Cr dissolved in the AlN delays the onset of a detrimental cubic-to-wurtzite phase transition to higher temperatures, up to above 1000 • C. Another alloy that have shown interesting high temperature properties is (ZrAl)N. [12][13][14][15][16][17][18] Also, alloying (TiAl)N with Zr have been shown to give improved high temperature properties.…”
Section: Introductionmentioning
confidence: 99%